Schriftexegese als Voraussetzung für Emil Brunners frühe dialektische Christologie anhand des Beispiels Mk 15,33–41 - STEINER, Fabienne (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2024)
Dialectical Christology Using the Example of Mk 15:33–41 In my article, I would like to show Emil Brunner’s early thoughts and statements included in his sermons in Obstalden among others. These sermons are unknown and unpublished to date. It is mostly claimed that Brunner entered in a modern and dialectical phase because of his colleague in the Reformed Church, Karl Barth. The truth is that they later had intense discussions about theses and antitheses in the phase of dialectics. Brunner, however, formulates new dialectical thoughts earlier than Barth does – for example, already in 1916 on dialectical Christology by using the text Mk 15:33–41 and reflecting arguments of modern theology. He speaks in his sermons about God (thesis), man (antithesis), and “Gottmensch” (synthesis).